Effects of molecular weight of polyaspartic acid on nitrogen use efficiency and crop yield. (18th July 2022) - Liu, Tai; Yang, Jinhui; Wang, Hongyuan; Chen, Yanxue; Ren, Jie; Lin, Xiaobo; Zhao, Junchai; Chen, Bingyi; Liu, Hongbin
Abstract: Background: In the past decades, ever‐increasing fertilizer use has led to a continuous increase in agricultural output. However, serious waste of resources occurs because of the low utilization of fertilizers. Polyaspartic acid (PASP) is a biodegradable polymer that can be used as a fertilizer synergist in agricultural production to improve the nutrient utilization capacity of plants. For polymers, the molecular weight (MW) often affects their effectiveness. However, little information is available on the effects of PASP MW in agriculture, especially on nitrogen leaching and plant element uptake. Results: This work was conducted to identify the effect of PASPs with three different MWs – PASP‐1 (MW: 5517), PASP‐2 (MW: 6934), and PASP‐3 (MW: 7568) – on nitrogen leaching, lettuce growth, and wheat cultivation. The results revealed that PASP favored plant growth and nitrogen accumulation in the soil, independent of crop species. PASP with a higher MW improved yields and the agronomic characteristics of lettuce and wheat. Furthermore, apparent amelioration of nitrogen use efficiency for lettuce (7.6%, 12.8%, and 15.0%) and wheat (4.6%, 8.1%, and 9.2%) was observed in the treatments with PASP addition. The effects and merits of PASPs on preventing ammonium nitrogen leaching and improving lettuce and wheat productivity were as follows: PASP‐3 > PASP‐2 > PASP‐1. Conclusion: The MW of PASP is an essential factor affecting inorganic nitrogen leaching and crop productivity, and PASP with a higher MW (7568) is recommended for application in agriculture. © 2022 Society of Chemical Industry.